A novel and versatile solar Borehole Thermal Energy Storage assisted by a Heat Pump. Part 1: System description. (May 2023) - Maragna, Charles; Rey, Charlotte; Perreaux, Marc
Abstract: The paper reports a system combining Solar Thermal Collectors (STC), Borehole Thermal Energy Storage (BTES), a Heap Pump (HP) and a backup boiler for space heating and Domestic Hot Water (DHW) production. The integration of the components and the overall control strategy are described. The system is flexible, being able to select the best thermal source and to use it directly or through a HP, while only the excess solar heat is stored into the BTES. The contribution of every subsystem to the energy mix is discussed. For a "reference configuration" combining the three subsystems ("Design D") and characterized by heating and DHW needs of 510.5 MWh.y −1 and 226.7 MWh.y −1 respectively, a BTES volume of 15000 m 3, a distance between boreholes of 3 m, a STC area of 2500 m 2, and a solar tank volume of 100 m 3, the system uses 274 units of gas and electricity to provide 1000 units of heating and DHW. This reference configuration outperforms any alternative design: Design A (STC only), Design B (STC and HP) and design C (STC and BTES) would respectively require 612, 480 and 591 units of gas and electricity to do so. A one-at-a-time analysis reveals that the STC area, azimuth and inclination, the solar tank volume, the BTES volume, the borehole density and the HP power are key parameters to the overall system performance. Graphical abstract: Image 1